PELAKSANAAN PERLINDUNGAN HUKUM TERHADAP ANAK DI BAWAH UMUR SEBAGAI KORBAN TINDAK PIDANA KEKERASAN SEKSUAL DI POLRES KARANGASEM - Ni Nyoman Adi Weda Astuti; Ni Komang Ratih Kumala Dewi (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2023)
Children are the nation's buds who have the potential to become the younger generation to continue the ideals of the nation's struggle who have a strategic role, and have special characteristics and characteristics that guarantee the continued existence of the nation and state in the future. One of the criminal acts that has become a phenomenon lately is the crime of sexual violence against minors. Child protection is all activities to ensure and protect children and their rights so that they can live, grow, develop and participate, as well as receive protection from violence and discrimination. The implementation of legal protection for minors as victims of sexual violence at the Karangasem Police is carried out by providing protection and assistance, hiding the victim's identity, cooperating with other institutions, handling fast, treating humanely by paying attention to needs according to their age, obtaining information Regarding the development of cases, rehabilitation assistance, all of that is based on the law.